The characteristics and analysis of polar compounds in deep-frying oil: a mini review - Cao, Xinyu; Li, Xue; Shu, Nanxi; Tan, Chin Ping; Yong, Jiang Xu; Liu, Yuanfa (Springer, 2022)
Deep frying is one of the most popular culinary processes, which induces oils generating a large number of polar compounds (PC) with complex structure, resulting in the difficulty of isolation and identification. In this review, we aimed to discuss the components of PC and then summary highly selective and highly sensitive approaches to analysis PC. It is found that infrared is the most convenient method for qualitative analysis, and chromatography is suitable for quantitative analysis, and electron spin resonance is applicable for mechanism analysis. In the future, sophisticated forecast technologies and comprehensive analytical methods will characterize the development trends in PC analysis, which will be beneficial for a full understanding of deep-frying oil food safety and quality control.